Crataegus monogyna Jacq., Sorbus aria (L.) Crantz and Prunus spinosa L.: From Edible Fruits to Functional Ingredients: A Review - Cristina Tamayo-Vives; María Úbeda; Patricia Morales; Patricia García-Herrera; María Cortes Sánchez-Mata (Foods, 2025)
Plants have historically served as key sources of nutrition and popular medicine, which persists in current applications. The increasing demand for natural bioactive compounds has intensified the incorporation of plant-derived ingredients in both the food and pharmaceutical industries. This narrative review focuses on the fruits of Crataegus monogyna Jacq., Sorbus aria (L.) Crantz, and Prunus spinosa L. (Rosaceae), traditionally utilized in Europe and characterized by a high content of phenolic compounds, flavonoids, and anthocyanins. These metabolites are associated with antioxidant, anti-inflammatory, and cardioprotective properties. The available literature on their phytochemical profiles, biological activities, and integration into the Mediterranean Diet is critically assessed. Evidence supports their potential as functional food components. Despite encouraging in vitro results, the scarcity of in vivo and clinical studies limits the translational potential of these findings. Further research is warranted to validate their efficacy and safety in human health. This review underscores the value of integrating traditional ethnobotanical and ethnopharmacological knowledge with contemporary scientific research to explore novel applications of these underutilized wild fruits.